PERAMPASAN HARTA BENDA DALAM TINDAK PIDANA PENCUCIAN UANG DILIHAT DARI SEGI HUKUM - Putra, Andrian Ananda (Cahaya Ilmu Bangsa, 2024)
ABSTRACT Money laundering is a crime that harms the public interest, causes economic instability in a country, and is more dangerous than corruption because tracking money flow from money laundering will be more difficult. When considering the impact, asset forfeiture is vital since it employs a